Managing Migration : Lessons from the Philippines - Ruiz, Neil G. (World Bank, Washington, DC, 2012)
This note provides a glimpse of the institutions built to manage migration in the Philippines. It describes how one country of origin government helps its migrants by regulating overseas employment recruitment, informing migrants of available resources abroad through a mandatory deployment process, providing protection and representation through a migrant welfare fund and absentee voting, and developing recording mechanisms to understand migrants' needs. Managing migration also comes with a price and governments need to develop a coordinated strategy to sustain such endeavors.